Vector competence of mosquitoes from Germany for Sindbis virus - Jansen, Stephanie; Lühken, Renke; Helms, Michelle; Pluskota, Björn; Pfitzner, Wolf Peter; Hoffmann, Sandra; Becker, Norbert; Schmidt-Chanasit, Jonas; Heitmann, Anna (Viruses, 2022)
Transmission of arthropod-borne viruses (arboviruses) are an emerging global health threat in the last few decades. One important arbovirus family is the Togaviridae, including the species Sindbis virus within the genus Alphavirus. Sindbis virus (SINV) is transmitted by mosquitoes, but available data about the role of different mosquito species as potent vectors for SINV are scarce. Therefore, we investigated seven mosquito species, collected from the field in Germany (Ae. koreicus, Ae. geniculatus, Ae. sticticus, Cx. torrentium, Cx. pipiens biotype pipiens) as well as lab strains (Ae. albopictus, Cx. pipiens biotype molestus, Cx. quinquefasciatus), for their vector competence for SINV. Analysis was performed via salivation assay and saliva was titrated to calculate the amount of infectious virus particles per saliva sample. All Culex and Aedes species were able to transmit SINV. Transmission could be detected at all four investigated temperature profiles (of 18 ± 5 °C, 21 ± 5 °C, 24 ± 5 °C or 27 ± 5 °C), and no temperature dependency could be observed. The concentration of infectious virus particles per saliva sample was in the same range for all species, which may suggest that all investigated mosquito species are able to transmit SINV in Germany.
Gesehen am 30.01.2023